2021
DOI: 10.1111/bph.15676
|View full text |Cite
|
Sign up to set email alerts
|

Subtype‐selective positive modulation of KCa2 channels depends on the HA/HB helices

Abstract: Background and Purpose: In the activated state of small-conductance Ca 2+ -activated potassium (K Ca 2) channels, calmodulin interacts with the HA/HB helices and the S4-S5 linker. CyPPA potentiates K Ca 2.2a and K Ca 2.3 channel activity but not the K Ca 2.1 and K Ca 3.1 subtypes.Experimental Approach: Site-directed mutagenesis, patch-clamp recordings and in silico modelling were utilised to explore the structural determinants for the subtypeselective modulation of K Ca 2 channels by CyPPA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…Our recent study has revealed that the subtype selectivity of CyPPA for K Ca 2.2a and K Ca 2.3 over K Ca 3.1 channels relies on the HA/HB helices. 33 We aligned the amino acid sequences of the rat K Ca 2.2a, human K Ca 2.3, and human K Ca 3.1 channel subtypes in the proximal C terminus ( Figure 2 A). Rat K Ca 2.2a has a valine residue (V420) equivalent to a methionine residue (M311) of the human K Ca 3.1 channel in the HA helix.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our recent study has revealed that the subtype selectivity of CyPPA for K Ca 2.2a and K Ca 2.3 over K Ca 3.1 channels relies on the HA/HB helices. 33 We aligned the amino acid sequences of the rat K Ca 2.2a, human K Ca 2.3, and human K Ca 3.1 channel subtypes in the proximal C terminus ( Figure 2 A). Rat K Ca 2.2a has a valine residue (V420) equivalent to a methionine residue (M311) of the human K Ca 3.1 channel in the HA helix.…”
Section: Resultsmentioning
confidence: 99%
“…The V-to-M and K-to-R discrepancies between the amino acid sequences of rat K Ca 2.2a and human K Ca 3.1 channels provide an explanation for the subtype selectivity of CyPPA. 33 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations